My Father’s Car Stranded in the Flooded Desert: Art Therapy in the Face of Climate Chaos - Stip, Emmanuel (Santé mentale au Québec)

(untitled) (Revue Santé mentale au Québec, 2025)
This reflective editorial essay emerges from a personal experience of being stranded for over 12 hours in a car during a sudden flood between Dubai and Abu Dhabi, an improbable confinement in the desert. As a psychiatrist, accustomed to listening and guiding others, I was instead confronted with my own stillness and isolation. In that immobility, I turned inward and found unexpected companionship in memory: the paintings of Philippe Lemaire, an artist I had met in a Montréal mental-health art workshop. For more than 2 decades, he has painted the same image, My Father’s Car, transforming repetition into resilience. In the desert’s silence, his work became my refuge. The patient’s art, once a therapeutic act, now offers healing to the physician. This essay reflects how art, repetition, and memory can bridge the distance between illness and care, and how art therapy, in a paradoxical reversal, can extend its grace to the healer. When glaciers melt and storms roar, the spectre of climate change sets its pace and the anguish of remaining immobile, or drowned grasps us and draws us closer to narrative medicine.